Discharge Summary Completion Timeliness and the Association of 30-Day Readmission. Issue 5 (May 2021) - Lewis, Patricia; Braddock, Kathryn; Tolaymat, Leila; Haga, Claire; Gillis, Melinda; Yin, Mingyuan; Dawson, Nancy
Abstract: Objective: This study aimed to review the association between timeliness to completion of a discharge summary to 30-day readmission to the hospital. Methods: This was a retrospective chart review of 109 patients discharged from Mayo Clinic Hospital. Results: Twenty-four of these patients were readmitted within 30 days. The time to completion of discharge summary was categorized for these readmissions to <72 hours: 15 (20%), between 72 hours and 7 days: 2 (11.1%), and >7 days: 7 (43.7%). There was no statistical significance for readmission for discharge summaries completed between 72 hours and 7 days compared with <72 hours ( P = 0.44). There was statistical significance correlating readmission within 30 days to the discharge summary completed >7 days compared with <72 hours ( P = 0.04). Conclusions: This study found that discharge summaries completed >7 days have an increased association with 30-day readmission rate. Abstract : Avoidable readmission is an established quality metric, and communication is key. This study evaluated whether timely discharge documentation was related to lower readmissions. The authors found that patients with discharge summaries completed longer than 7 days after discharge had a significantly higher readmission rate than those completed within 7 days.